TASAWUF VALUES DALAM TRADISI NYADRAN BAGI MASYARAKAT DESA SUMBERDAWE KECAMATAN MARON KABUPATEN PROBOLINNGO - Mukarromah, Silfiatun; Rusly, H. Fathullah; Islam, Saiful (Jurnal Al-Fatih, 2025)
The Nyadran tradition, as part of the local culture of Sumberdawe Village, not only has social dimensions but also contains spiritual values closely related to the teachings of Sufism in Islam. This study aims to examine how Sufi values are manifested in the implementation of the Nyadran tradition and how this tradition plays a role in shaping the spiritual awareness of the community. The main problem in this study is the lack of understanding among the community about the esoteric meaning (batiniah) of the Nyadran tradition, which is often only seen as a ritual inherited from ancestors. The method used in this study is a qualitative approach with observation techniques and in-depth interviews. The results show that the Nyadran tradition contains Sufi values such as ikhlas (sincerity of heart), tawakal (submission to Allah), zuhud (simple living), and mahabbah (love for others and ancestors). These values are reflected in the practice of charity, joint prayer, pilgrimage to graves, and the spirit of community togetherness. The conclusion of this study is that the Nyadran tradition is not just a customary ritual but also a vessel for internalizing Sufi values that strengthen the spirituality and social ethics of the Sumberdawe Village community.